Specialised English new directions in ESP and EAP research and practice - Hyland, Ken; Wong, Lillian L. C. 1970- (London Routledge, 2019)
"Specialised English: New Directions in ESP and EAP Research and Practice provides an authoritative and cutting-edge account of the latest avenues of research and practice in the dynamic field of Specialised English. Ken Hyland and Lillian Wong present 17 specially commissioned chapters by some of the world's leading experts to offer discussions of key topics in research, theory and pedagogy from a variety of international perspectives. Divided into three sections which focus on conceptual issues, text, and classroom practice, this book: Offers a clear and accessible introduction to current issues in EAP and ESP, including academic interaction, academic lingua franca, second language publishing, workplace talk, practitioner identity, data-driven learning and critical thinking; Includes studies of a range of genres such as research articles and student reports, student spontaneous speech, personal statements, builders' diaries and university tutorials; Presents links between theory and practice with a sampling of different research methodologies, practical applications and theoretical approaches. Specialised English is essential reading for upper-level undergraduate and postgraduate students and researchers in EAP/ESP and applied linguistics, as well as pre-and in-service teachers and teacher educators"--Provided by publisher.
Preface / Brian Paltridge -- Introduction / Ken Hyland & Lillian L.C. Wong -- Academically speaking: English as the lingua franca / Anna Mauranen -- What do we mean by "workplace English?" : a syllabus framework for course design and assessment / Jane Lockwood -- Genre as interdiscursive performance in English for professional communication / Vijay K. Bhatia -- Power in English for academic purposes / John Flowerdew -- EAP practitioner identity / Alex Ding -- Academic interaction: where's it all going? / Ken Hyland -- Exploring critical thinking in academic and professional writing : a genre-based approach / Ian Bruce -- Vocabulary in university tutorials and laboratories : corpora and word lists / Avril Coxhead & Thi Ngoc Yen Dang -- Researching the impact of "the culture order" in professional workplace contexts / Janet Holmes -- Multimodal student texts : implications for ESP / Jean Parkinson -- Grappling with the personal statement : transformation, appropriation, and externalization / Ann M. Johns -- Tools and strategies for data-driven learning (DDL) in the EAP writing classroom / Laurence Anthony -- Implementing disciplinary data-driven learning for postgraduate thesis writing / Lillian L.C. Wong -- English as a lingua franca and learner English in disciplinary writing : a corpus perspective / Lynn Flowerdew -- Academic writing feedback : collaboration between subject and EAP specialists / Jill Northcott -- Directives in academic writing tutorials : how do different teaching styles affect their use? / Ursula Wingate and Eva Ogiermann -- Seeking supervisor collaboration in a school of sciences at a Chinese university / Yongyan Li and Margaret Cargill.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- Foreign speakers; English language -- Technical English -- Study and teaching; English language -- Business English -- Study and teaching; Business writing; Academic writing